Construction and utilisation of a bidirectional reporter vector in the analysis of two nod-boxes in of Rhizobium loti : a thesis presented in partial fulfilment of the requirements for the Degree of Master of Science in Molecular Genetics at Massey University - Parry, Simon Keith (Massey University, 1993)
The nod-box is a 47bp cis-acting regulatory region which has been conserved amongst every species of Rhizobium studied to date. In species such as R. meliloti and R. leguminosarum, the nod-box has been shown to promote constitutive activity towards the regulatory nodD gene, and flavonoid-inducible expression towards the divergently-transcribed nodABCIJ operon. This bidirectional regulation of the so-called common nod genes was not observed in R. loti. A previous analysis of this species had shown that its nod-box promoted inducible activity towards the truncated 'nodD' gene, as well as the nodACIJ operon. It was the unusual arrangement of these R. loti nod genes that had initially aroused interest in this bacteria. To further investigate the role of the nod-box in the regulation of the R. loti common nod genes, a bidirectional reporter vector (pSPV4) was constructed. This novel vector allowed the promoter activity of a cloned nod-box-containing fragment to be concurrently measured in either direction using the same culture of cells. To achieve this construct, the gusA gene from pRAJ260 was blunt-end ligated into pUC21. An in-frame ribosome binding site (rbs) was cloned upstream of the gusA coding sequence to facilitate transcriptional fusions. The rbs and gusA gene were later excised as a functional unit and blunt-end ligated into pMP220 alongside the B-galactosidase reporter gene but in the opposite orientation. Hence, both reporter genes could be divergently transcribed from a common regulatory region cloned into the multiple cloning site that separated the genes. The fragments of DNA that were eventually cloned into the bidirectional vector were generated through the polymerase chain reaction. Each DNA insert contained the nod-box bracketed by differing lengths of flanking region. Once these PCR-generated fragments had been sequenced in pUC118 and subcloned into pSPV4, the resulting constructs were transformed into R. loti cells by electroporation. As the electroporation of these cells had not previously been reported, the conditions for this procedure were established and optimised. The results obtained from the bidirectional reporter assays disagreed with those observed in the earlier assays by Teo (1990). Neither the nodACIJ nod-box of NZP2037 nor the nodB nod-box of NZP2213, showed bidirectional inducible expression. In fact, both nod-boxes showed constitutive expression in the 'nodD' direction and inducible expression in the opposite direction. This indicates that the control of the nod genes in R. loti is fundamentally the same as that seen in other fast-growing Rhizobium species. Three regulatory elements affecting the levels of nod gene expression have tentatively been identified outside the nod-box sequence, though the results indicating their presence may simply be·due to spacing differences between the nod-box and the reporter gene.
Keywords: Nitrogen fixing microorganisms; Genetics; Rhizobium